SINGLE-MOLECULE DETECTION AND MANIPULATION WITH BIOLOGICAL NANOPORES - SCHIOPU, Irina; ASANDEI, Alina; MEREUTA, Loredana; DRAGOMIR, Isabela; BUCATARU, Cezara; LUCHIAN, Tudor (Studia Universitatis Babeș-Bolyai Chemia, 2021)
Single-molecule electrophysiology techniques using protein-based or solid-state nanopores as nanoreactors were proven incredibly useful as platforms for sensing and biophysical characterisation of biological molecules (e.g., peptides, proteins), DNA detection and sequencing in a label-free, low-cost, rapid and high signal-to-noise ratio manner. Herein we present a number of discoveries in this field, developed over the years in our laboratory, including: (i) the pH-mediated, fine-tuning of peptides passage through the α-hemolysin nanopore; (ii) increase of the capture rate and dwell times of polypeptides inside the nanopore, through engineering dipole-like polypeptides; (iii) the implication of a nanopore-AuNP (citrate anion-coated gold nanoparticles) platform to selectively detect nanomolar concentrations of target ssDNA.